2003
DOI: 10.1080/00050060310001707047
|View full text |Cite
|
Sign up to set email alerts
|

How unpopular are we? Reassessing psychologists' public image with different measures of favourability

Abstract: Psychologists in Australia have tended to survey theirpublic image with specific questions, such as how useful psychologists are, or how willing people are to consult them. While responses to these questions have generally implied an unfavourable public impression of psychologists, research in the United States has shown that psychologists are perceived less favourably on direct measures of favourability (e.g., specific questions), than on indirect indicators (e.g., overall favourability ratings). To reassess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
2
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 12 publications
1
23
2
4
Order By: Relevance
“…In den Medien sind "Psychos" meist in mittlerem Alter (Gharaibeh 2005), genauer, sie sind oft identisch mit dem (älteren) Sigmund Freud: Fast in der Hälfte der Fälle in denen "Psychos" auf Zeitschriftentitelbildern abgebildet waren, wurde sein Konterfei eingesetzt (Sydow et al 1998a) -bis heute ist das so. Sowohl Laien als auch Medizin-und Psychologiestudierende stellen sich das Aussehen von Psychotherapeuten und Psychologen häufig auch Sigmund-Freud-artig vor; sie beschreiben oft einen Mann im mittleren Alter, mit Bart und Brille, weniger werdenden grauen oder weißen Haaren und seriöser Kleidung (Barrow 2000;Dudley 1994;Gabbard u. Gabbard 1989;Gharaibeh 2005;Hartwig 2002Hartwig /2003Sydow et al 1998a;Sydow et al 1998b;Szykiersky u. Raviv 1995;Wahl u. Rietz 1999).…”
Section: Aussehenunclassified
See 1 more Smart Citation
“…In den Medien sind "Psychos" meist in mittlerem Alter (Gharaibeh 2005), genauer, sie sind oft identisch mit dem (älteren) Sigmund Freud: Fast in der Hälfte der Fälle in denen "Psychos" auf Zeitschriftentitelbildern abgebildet waren, wurde sein Konterfei eingesetzt (Sydow et al 1998a) -bis heute ist das so. Sowohl Laien als auch Medizin-und Psychologiestudierende stellen sich das Aussehen von Psychotherapeuten und Psychologen häufig auch Sigmund-Freud-artig vor; sie beschreiben oft einen Mann im mittleren Alter, mit Bart und Brille, weniger werdenden grauen oder weißen Haaren und seriöser Kleidung (Barrow 2000;Dudley 1994;Gabbard u. Gabbard 1989;Gharaibeh 2005;Hartwig 2002Hartwig /2003Sydow et al 1998a;Sydow et al 1998b;Szykiersky u. Raviv 1995;Wahl u. Rietz 1999).…”
Section: Aussehenunclassified
“…Früher galt in US-amerikanischen Comics auch ein europäisches Diplom an der Wand als obligatorisch (Hartwig 2002(Hartwig /2003Sydow et al 1998b;Wahl u. Rietz 1999). Studierende halten meist ein einzeltherapeutisches (im Sitzen) oder ein psychoanalytisches Setting (Couch) für typisch.…”
Section: Arbeitssettingunclassified
“…Psychology's public image is considered a two‐dimensional process comprising popularity (i.e., how favourably members of the public regard psychology and psychologists) and understanding (i.e., how informed members of the public are about psychology and psychologists) (Benjamin, 1986). A poor public image may not only affect the well‐being of psychology and psychologists, but also impact on the profession's capacity to serve and assist the wider community (Grant et al., 2008; Hartwig & Delin, 2003).…”
mentioning
confidence: 99%
“…Unlike studies conducted in the USA that have revealed a positive public impression of psychologists (Benjamin, 1986; McGuire & Borowy, 1979; Murstein & Fontaine, 1993; Nunnally & Kittross, 1958; Webb, 1989; Webb & Speer, 1986), Australian research has yielded a more conservative profile (Hopson & Cunningham, 1995; Sharpley, 1986; Small & Gault, 1975; Wilkinson et al., 1978). While the specific methodological approach employed may account for such differences (Hartwig & Delin, 2003), Australian public opinion research has been limited by several factors. First, in no Australian studies were counselling psychologists included in the experimental sample.…”
mentioning
confidence: 99%
See 1 more Smart Citation